The Opportunity of Ai Technology to Increase The Value Chain of Oil Palm Plantation - Sediyono, Agung; Solihah, Binti (Penerbitan Universitas Trisakti, 2025)
Indonesia produced 58,4% of worldwide oil palm production, and the contribution of the plantation sub-sector in 2022 is 3,76% of PDB and 30,32% of the Agriculture, Forestry, and Fishery sectors. However, oil palm production in Indonesia is lack of productivity and efficiency compared to other countries, especially Malaysia. Therefore, this paper tries to explore the opportunities of AI technology to increase the value chain of the oil palm plantation, especially in productivity and efficiency. The scope of exploration started from oil palm seeding, nursery, planting, and harvesting. Based on the oil palm plantation value chain review and the previous research works in AI implementation on value chain respectively, it can be concluded that AI technology has been explored to be implemented in oil palm plantations intensively. However, there is still enough room for improvement especially in accuracy rate and adoption feasibility for smallholder planters. Moreover, IoT and drone technology have a big potential to be adopted because the plantation is mostly hard-to-reach areas by humans, for instance high oil palm bunch, long distance journey for inspection and maintenance, wild animal threat, etc.